Colloid cyst with septum pellucidum agenesis: A case report and revıew of the literature - (:unkn) unknown (My University, 2007)
37 yaşında erkek hasta ani başlayan şiddetli başağrısı ve kusma şikayetleri ile kliniğimize başvurdu. Gözdibi muayenesinde intrakraniyal basınç artışının bir bulgusu olarak papilödem saptandı. Kraniyal magnetik rezonans görüntülemede 3. ventrikülde, gadolinyum tutan kistik lezyon ve septum agenezi saptandı. Transkollazal interhemisferik yaklaşımla kist tamamen çıkarıldı. Patoloji olarak kolloid kist tanısı kondu. Yoğun bakımda bir gün takip edilen hasta, postoperatif 4 günde taburcu edildi. Altıncı ayda yapılan kontrolünde nörolojik muayenesi normal sınırlarda bulundu. Bu vaka literatürdeki 2. kolloid kist ve septal agenezis vakası ve ilk intrakraniyal basınç artışı ile bulgu veren vaka sunumudur.

A 37-year-old man was admitted to our clinic with sudden onset of severe headache and vomiting. Fundoscopic ophthalmic examination revealed papiledema as a sign of increased intracranial pressure. Cranial magnetic resonance imaging revealed homogenous gadolinium enhanced cystic lesion in the third ventricle and agenesis of the septum pellucidum. Transcallosal interhemispheric approach was performed and cystic lesion was excised totally. Pathological diagnosis was a colloid cyst. After one-day intensive care, the patient was discharged on postoperative day 4. His neurological examination was normal after six-month follow-up. This report represents the second report of colloid cyst and septal agenesis, and a first report of treatment of colloid cyst with this syndrome.
Septum pellucidum agenezinin eşlik ettiği kolloid kist: Vaka sunumu ve literatür taraması
Keywords: Genel ve Dahili Tıp